Geo-Quantitative Analysis of Violent Crime Intervention Strategies in Kaduna State, Nigeria - Olanrewaju Yusuf Yahaya; Andrew Egba Ubogu; Garba K/Naisa Adamu; Abdulrashid Ibrahim; Nurudeen Adesola Malik (Geosfera Indonesia, 2023)
The complexities and consequences of violent crimes require a robust and effective approach to achieve a sustainable reduction of violence in our society. This paper, therefore, presents an avenue to provide the geo-quantitative analysis of violent occurrences in Kaduna State of Nigeria to determine the pragmatic interventionist strategies for managing violent crime incidence among the people of the study area. Geo-quantitative analysis entails transforming numerical data about criminal activities into a map of proportional circles to depict the distribution pattern of criminal activities and using scree plots and factor loading to show higher-order intervention measures for managing violent crimes. Five Local Government Areas (LGAs) with relatively high levels of violent incidence were purposively selected while snowball sampling method was used to administer questionnaires to 384 respondents. From the findings, the spatial distribution of violent crimes revealed that Birni-Gwari and Kachia LGAs accounted for the highest incidence of kidnapping and village raids respectively while Kajuru LGA is known for the highest cases of cattle rustling and armed robbery. The critical interventions in managing violent crimes are reconciliation efforts to restore order and normalcy, negotiation between aggrieved parties, and adoption of a traditional conflict resolution system with a rotated factor matrix of 0.828, 0.581, and 0.544 respectively. Furthermore, the strongest positive correlation exists between good government policies and equity with fairness in representation and establishment of developmental projects (r = 0.524, and p Ë‚ 0.001). Therefore, the study recommended establishing conflict mediation centers across the communities. Similarly, it is essential to have a good governance system that will give people their fair share of national resources and adequate policing of communities that could guarantee the reduction of violent incidents to the barest minimum.